Exploring the Role of Green Grass Jelly Leaf Pectin as a Natural Additive in Integrated Science Education: A Narrative Study - Manasikana, Oktaffi Arinna; Moreira, Ilidio Ximenes (LPPM Universitas Hasyim Asy'ari Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study examines the potential of pectin from green grass jelly (Cyclea barbata) leaves in industrial and educational applications. Pectin, as a natural thickening agent, shows good quality in food products such as jam, jelly, and gel-based drinks, providing a healthier and more environmentally friendly alternative compared to synthetic thickeners. In addition, green grass jelly pectin also has potential in non-food applications, such as biopolymers in the oil and pharmaceutical industries, providing a more sustainable solution in the polymer flooding process and the development of medical biomaterials. This study also explores the role of pectin in integrated science learning, by integrating STEM (Science, Technology, Engineering, and Mathematics) and ethnoscience approaches to improve students' understanding of scientific concepts and practical applications of science based on local natural resources. Through project-based experiments, students can understand the pectin extraction process and its application in real life. This pectin-based learning model also supports 21st-century skills, such as critical thinking, problem solving, and creativity. Overall, green grass jelly leaf pectin offers great potential in supporting industrial sustainability as well as education that is more contextual and relevant to current environmental challenges.